MicroRNA in innate immunity and autophagy during mycobacterial infection. (28th November 2016) - Kim, Jin Kyung; Kim, Tae Sung; Basu, Joyoti; Jo, Eun‐Kyeong
Abstract: The fine‐tuning of innate immune responses is an important aspect of host defenses against mycobacteria. MicroRNAs (miRNAs), small non‐coding RNAs, play essential roles in regulating multiple biological pathways including innate host defenses against various infections. Accumulating evidence shows that many miRNAs regulate the complex interplay between mycobacterial survival strategies and host innate immune pathways. Recent studies have contributed to understanding the role of miRNAs, the levels of which can be modulated by mycobacterial infection, in tuning host autophagy to control bacterial survival and innate effector function. Despite considerable efforts devoted to miRNA profiling over the past decade, further work is needed to improve the selection of appropriate biomarkers for tuberculosis. Understanding the roles and mechanisms of miRNAs in regulating innate immune signaling and autophagy may provide insights into new therapeutic modalities for host‐directed anti‐mycobacterial therapies. Here, we present a comprehensive review of the recent literature regarding miRNA profiling in tuberculosis and the roles of miRNAs in modulating innate immune responses and autophagy defenses against mycobacterial infections.